THE MEANING OF TRUST IN SURAT AL- AHZAB VERSE 72 THE PERSPECTIVE OF SHEIKH USTMAN AL-KHUBAWI - Wahyu Widodo; Roni Susanto; Deden Hidayat (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
Trust is a right given by Allah to every mukhalaf that must be maintained and accounted for. Today mukhalaf understand theoretically the meaning of trust but inversely proportional to the practical realm. Practical problems can be proven by not a few Muslims who have not carried out sharia orders such as leaving prayers, fasting and talking about other people's badness. This certainly causes harm to oneself both in the world and in the hereafter, so that a solution step is needed to provide an understanding of the meaning of trustworthiness to the general public. The purpose of this study is to reveal the meaning of trust in Surah al-Ahzab verse 72 based on the perspective of Sheikh Ustman al-Khubawi. The method used in this research is to use library research style, and the method used is thematic interpretation method (Maudhû'îy). Primary sources in this study are the book of Durrotunnasihin, Tafsir Ibn Kathir, Tafsir Ar-Razi, Tafsir Jalalain, Tafsir Al-Qutubi. While secondary sources are articles related to the interpretation of Surah al-ahzab verse 72. The results of this study indicate that the trust according to Sheikh Ustman al-Khubahi in the book of Durrotunnasihin includes: first keep the prayer, second keep the limbs,. Third carry out fasting. Fourth, pay zakat. Fifth hajj and Sixth maintain the family.